Revealing Characterization of Clive Durham in Maurice (1987) Movie Through an Analysis of Illocutionary Acts: A Study of Speech Acts - Wulandari, Dianita; Wulandari, Dwi (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
This study aims to unfold the characterization of Clive Durham portrayed in Maurice (1987) movie directed by James Ivory by analyzing his utterances using the speech acts theory proposed by Searle. In analyzing the data, the writer considers the context of the utterances and the implicit message conveyed by Clive Durham to acknowledge his characterization. The result shows that there are three types of illocutionary acts performed by Clive Durham which are classified into assertive, directive, and expressive. Based on the analysis, Clive Durham is the typical person who is assertive, afraid of social judgment, has the audacity to express his thoughts and feelings, and knows how to behave politely and considerately.Â